Muscular characters in the phylogeny of Liolaemus (Squamata: Iguania: Liolaemidae): a reappraisal - Abdala, Virginia Sara Luz (2006)
Liolaemus is one of the most speciosus genera of lizards, having more than 200 species. It iscomposed of small to moderate-sized lizards that live throughout most of austral South America.Many groups whose phylogenetic relationships have been controversial compose the genus. Theproposed phylogenetic relationships of these lizards have been based on data-sets from manysources. In all of the morphological data-sets, three myologycal characters have been consideredparticularly important:1) insertion of the m. tibialis anticus hypertrophied in association with thepresence of a sharp, bladelike process of the tibia, 2) medial head of the m. flexor tibialis internuscovered by a hypertrophied m. puboisquitibialis, and 3) presence of melanic pigment within themedial portion of the epimysium of the m. pterygomandibularis. Important taxonomic andanatomical questions about these characters remain: 1) Can the size of the m. puboisquiotibilis bescored with only two character states? 2) Is there a close relationship between the hypertrophied m.flexor tibialis internus and the patch of the enlarged proximal postfemoral scales? and 3) Are thesemuscular characters exclusive to some of the groups of Liolaemus that have been proposed?Focusing on these questions, we have conducted a taxonomic and anatomic review of thesecharacters in 42 species representing all of the proposed groups of Liolaemus. The analyzedsamples show that variations in the considered muscular characters are much more gradual thanpreviously stated. The only exception is the insertion of the m. tibialis anticus hypertrophied inrelation to a bladelike hypertrophy of the tibia, which characterizes the montanus group of Etheridge (1995). These characters seem to have the same phylogenetic information as any othermorphological character. Although the coding we used is more complex, it shows more preciselythe subtlety of the change in the character states.